Osteotomy Gap Consolidation in Dogs after Tibial Tuberosity Advancement with and without Cancellous Bone Graft - Ferrigno, Cassio Ricardo Auada; Poletto Ferreira, Márcio; Cunha, Olicies da; Caquias, Daniela Fabiana Izquierdo; Santos, Jaqueline França dos; Souza, Alexandre Navarro Alves de; Yamauchi, Kelly Cristiane Ito; Ferraz, Vanessa Couto de Magalhães; Verpaalen, Valentine (Acta Scientiae Veterinariae, 2025)
Background: Cranial cruciate ligament disease is the leading cause of lameness in dogs. The application of autogenous cancellous bone graft within the osteotomy gap has been indicated to accelerate bone healing, but prospective clinical studies evaluating the effects of autogenous cancellous bone graft on osteotomy gap healing after TTA have produced mixed results. The aim of this study was evaluate bone healing time in dogs with cranial cruciate ligament disease that underwent osteotomy for tibial tuberosity advancement with or without autogenous cancellous bone graft. We hypothesized that an autogenous cancellous bone graft would accelerate bone consolidation after tibial tuberosity advancement. Materials, Methods & Results: A total of 30 dogs (8 male; 22 female) of various breeds with unilateral or bilateral cranial cruciate ligament disease (CCLD), a minimum weight of 20 kg (44 lbs), and a tibial plateau angle up to 25° were randomly assigned to Group A [15 dogs; graft] or B [15 dogs; control]. Dogs underwent tibial tuberosity advancement (TTA) with [Group A] or without [Group B] autogenous cancellous bone graft harvested from their tibia. All surgical procedures were performed by the same experienced orthopedic surgeon. They were assessed through monthly radiographs (at postoperative [PO] day 30, 60, 90, and, as required to cover complete healing, 120, 150, 180, and 210 days). Radiographic evaluation was conducted by an experienced veterinarian who was familiar with the TTA procedure and was blinded to the treatment group (images without identification - name/group). Significantly more dogs in Group A achieved 100% osteotomy gap consolidation at 30 days PO (P = 0.0002) and 60 days PO (P = 0.0016) than Group B. The average time to 100% bone consolidation was 56 days (± 15.4) for Group A and 108 days (± 46.47) for Group B, and was significantly shorter for group A (P < 0.0001). Discussion: Our results have showed bone consolidation time in dogs with CCLD undergoing the surgical technique of TTA is significantly faster when aided by an autogenous cancellous bone graft at 30 and 60 days PO. Therefore, we accept our hypothesis that autogenous cancellous bone graft accelerates bone consolidation. These results support the findings of another study, that noted that the use of autograft resulted in significantly higher osteotomy healing scores at 6 and 10 weeks postoperatively. The divergence of results between studies evaluating osteotomy gap consolidation following TTA may be partly explained by the subjective and different methods of bone consolidation evaluation used in these investigations. This is a standard limitation when using radiographic evaluation, however, the selection of this method is justified by the fact that this imaging modality is commonly used in routine clinical practice to evaluate bone consolidation – it is, therefore, clinically representative. The present study is subject to certain limitations. Firstly, variables other than bone graft treatment may have influenced bone consolidation time, such as age, weight, and cage size. However, these variables were not significantly different between the evaluated groups (P > 0.05), thus eliminating the effects of these potentially confounding variables. Secondly, the investigator evaluating radiographic bone consolidation could not be completely blinded to the treatment group, as some degree of radiation attenuation was associated with the cancellous bone graft. In conclusion, one consolidation time in dogs with CCLD undergoing the surgical technique of TTA is significantly faster when aided by an autogenous cancellous bone graft. Keywords: stifle, knee, TTA, cranial cruciate ligament, rupture.